The value of intracranial pressure monitoring in acute hemispheric stroke - Schwab, Stefan; Aschoff, Alfred; Spranger, Matthias; Albert, Friedrich; Hacke, Werner (Neurology, 1996)
Background and purpose: Persistently elevated intracranial pressure (ICP) has been associated with poor clinical outcome after severe brain injury, such as neurotrauma, intracerebral hemorrhage, and subarachnoidal hemorrhage. Although ICP monitoring is increasingly being used in intensive care treatment of patients with ischemic stroke, its value has not been established. Patients and methods: The clinical course of 48 patients with the clinical signs of increased ICP due to large hemispheric or middle cerebral artery territory infarction defined by CT and subjected to ICP monitoring was prospectively evaluated. Epidural ICP probes were inserted ipsilaterally to the site of primary brain injury in all and also contralaterally in seven patients. Initial clinical presentation was assessed by the Scandinavian Stroke Scale (SSS) and the Glasgow Coma Score (GCS). All patients were treated according to a standardized treatment protocol for elevated ICP. ICP values were correlated with the clinical presentation at the time point of deterioration, with outcome, and with CT findings. Different treatment strategies to lower ICP were analyzed as to their effectiveness. Results: Only nine of the 48 patients survived the infarct (19%). The cause of death was transtentorial herniation with subsequent brain death in all 39 patients. The patients' mean SSS on admission was 20.6 (survivors 21.5 +/- 5.6, nonsurvivors 19.8 +/- 6.5). In all patients clinical signs of herniation preceded the increase in ICP. Patients with ICP values >35 mm Hg did not survive. CT changes did not always correspond with the measured ICP values. All medical strategies to lower ICP, including osmotherapy, hyperventilation, THAM-buffer, and barbiturates, were initially effective, but only in a minority of patients was ICP control sustained. Conclusions: ICP monitoring of large hemispheric infarction can predict clinical outcome. Pharmacologic intervention had no sustained effect. ICP monitoring was not helpful in guiding long-term treatment of increased ICP. It remains doubtful that ICP monitoring in acute ischemic stroke has a positive influence on clinical outcome. - NEUROLOGY 1996;47: 393-398